2016
DOI: 10.1007/s40797-016-0028-9
|View full text |Cite
|
Sign up to set email alerts
|

The Drivers of Italy’s Investment Slump During the Double Recession

Abstract: This paper examines the causes of the exceptionally marked fall in nonconstruction investment in Italy since 2007. In terms of sector-specific contributions, non-financial private services accounted for most of the decline in the aggregate investment rate, but the reallocation of value added away from industry was also a drag on investment. In concordance with survey findings, an aggregate econometric model of investment indicates that even during the recent double recession the most important driver of capita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…It is a measure of diagreement across firms concerning their economic outlook. Source: calculations on the European Commission Business Survey data using the methodology described in Busetti;Giordano and Zevi (2016).…”
Section: Cyclical Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a measure of diagreement across firms concerning their economic outlook. Source: calculations on the European Commission Business Survey data using the methodology described in Busetti;Giordano and Zevi (2016).…”
Section: Cyclical Conditionsmentioning
confidence: 99%
“…Moreover, we introduce for the first time in the literature a comparable cross-country sector-specific survey-based uncertainty measure for sectors other than manufacturing. Following Fuss and Vermeulen (2008), Bachmann, Elstner and Sims (2014) and Busetti, Giordano and Zevi (2016), we proxy demand uncertainty with the cross-sectional dispersion in the expectations of firms interviewed in the monthly European Commission Business Survey. The measure is computed as � + + − − ( + − − ) 2 , where + and − are the fractions of firms with "increase" and "decrease" responses at time t, and varies between 0 and 1.…”
mentioning
confidence: 99%
“…These three series are found to be integrated of order one according to the two standard unit root/stationarity tests, the Augmented Dickey-Fuller test (Dickey and Fuller, 1979) and the Kwiatkowski-Phillips-Schmidt-Shin (KPSS) test (Kwiatkowski et al, 1992), as shown in Appendix A.1. This result is quite standard in the empirical studies replicating the Hall and Jorgenson (1967) model, such as Bussière et al (2015), Busetti et al (2016) and Fatica (2018). 1…”
Section: Forecasting Modelsmentioning
confidence: 59%
“…Several studies (Bontempi et al, 2010;Busetti et al, 2016;Bacchini et al, 2018;Giordano et al, 2019) have focused specifically on Italy, an insightful case-study in that, after growing at a comparable rate to its peer euro-area economies since 1995 (the initial year of official national account data), Italy's GFCF then experienced a significantly more pronounced downturn during the double recession and a more sluggish recovery thereafter. In this country, non-financial corporations (which we loosely also refer to as "firms" in this article) alone undertake about half of total GFCF (Giordano et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Each sector can contribute to the investment-to-output ratio dynamics in two ways: by changes in investment within the sector (within-effect) and by changes in the share of the sector in aggregate output (between-effect, or structural shift). To decompose the contributions into within-and between-effects, we follow the shift-share methodology (see Busetti andothers 2016 andEC 2017, among others).…”
Section: With a Similar Downward Shift Observed In Individual Secmentioning
confidence: 99%